Substituent effects on the structure of [Ag(py-R)n](NO3) ionic pairs: structural and computational studies; CrystEngComm; Vol. 27, iss. 48 - Radyush E. A. Ekaterina Alekseevna; Sinelnikov G. O. Gleb Olegovich; Shurikov M. K. Matvey Konstantinovich; Shamshurin M. V. Maksim Vladimirovich; Semenov N. A. Nikolay Aleksandrovich; Postnikov P. S. Pavel Sergeevich; Sokolov M. N. Maxim; Abramov P. A. Pavel Aleksandrovich (2025, 2025)
Title screen